A novel synthetic isothiocyanate ITC-57 displays antioxidant, anti-inflammatory, and neuroprotective properties in a mouse Parkinson's disease model. (30th November 2016) - Lee, Ji Ae; Son, Hyo Jin; Kim, Ji Hyun; Park, Ki Duk; Shin, Nari; Kim, Hye Ri; Kim, Eun Mee; Kim, Dong Jin; Hwang, Onyou
Abstract: The degenerative process of the nigral dopamine(DA)rgic neurons in Parkinson's disease (PD) involves both oxidative stress and neuroinflammation. In the present study, we aimed at developing a novel antioxidant and anti-inflammatory agent for PD therapy. Toward this end, we screened a novel focused library of isothiocyanate derivatives that we have generated for an anti-inflammatory property. We obtained a novel compound ITC-57 and found that ITC-57 effectively induced gene expression of the antioxidant enzymes NAD(P)H quinone oxidoreductase-1, the catalytic and modulatory subunits of glutamylcysteine ligase, and HO-1 in DAergic neuronal CATH.a cells and protected CATH.a cells from oxidative damages. The compound also induced the same antioxidant enzymes in microglial BV-2 cells and suppressed the production of the proinflammatory molecules nitric oxide, interleukin-1β (IL-1β) and tumor necrosis factor-α (TNF-α) in lipopolysaccharide-activated BV-2 cells. In the 1-methyl-4-phenyl-1, 2, 3, 6-tetrahydropyridine (MPTP)-elicited mouse model of PD, ITC-57 protected the DAergic neurons from degeneration, induced HO-1, lowered TNF-α, and suppressed microglial activation in the nigra. Furthermore, ITC-57 prevented the PD-associated motor deficits from occurring. Taken together, ITC-57 would be useful toward development of a disease-modifying therapy for PD.